If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + -26 = p Reorder the terms: -26 + 2p = p Solving -26 + 2p = p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -26 + 2p + -1p = p + -1p Combine like terms: 2p + -1p = 1p -26 + 1p = p + -1p Combine like terms: p + -1p = 0 -26 + 1p = 0 Add '26' to each side of the equation. -26 + 26 + 1p = 0 + 26 Combine like terms: -26 + 26 = 0 0 + 1p = 0 + 26 1p = 0 + 26 Combine like terms: 0 + 26 = 26 1p = 26 Divide each side by '1'. p = 26 Simplifying p = 26
| 4(x-3)+18=3(x+3) | | 2x-3(x-5)=7 | | 6b-61=b+4 | | 6(3n-7)=84 | | 2x^4/5=25 | | x(x+2)=x(5+x) | | 10a+4(a+1)=32 | | 7(6+7a)= | | x^4+8x^3+14x^2-17x-42=0 | | -6+8(8a-8)= | | 3x-6+1x+30=7+8x+23-6x | | 42/168 | | 17x+4=x+35 | | 17v+58=3v+86 | | 2q=q+13 | | -10q-4q-6=18 | | 8v+4v= | | 10x-3(x-9)=9(x-1)+1 | | 2y-50=y-17 | | 6(9+11v)= | | -5n-6=7n+6 | | -3(4v-2)+v=4(v+3) | | a-b/9 | | 3u-62=4u-91 | | 6-1y=-2.3 | | 144=12(x-5) | | 80=23-3u | | 5[4x+6]=6x+9 | | -2r+1=-4r+9 | | Y=2r+5 | | 12-a/36=47 | | n+20n=5(n+20) |